Community Participation: Improve Management of Public Relations with Business and Industry - Yuannita, Nina; Ayu, Sovia Mas; Amiruddin, Amiruddin; Fatimah, Siti (Universitas Islam Negeri Raden Intan Lampung, 2023)
Collaboration programs between educational institutions and the business world and the industrial world include curriculum validation and synchronization, industrial visits, apprenticeship or industrial practice programs, training programs, vocational competency tests, production programs and graduate distribution programs. This study uses a qualitative descriptive approach. Data collection techniques with interviews, observation and documentation. Data analysis uses data reduction, data presentation and conclusions. Test the validity of the data using source triangulation and technical triangulation. The results of this research show that vocational high school 3 bandar lampung, Indonesia, has implemented public relations management with the business world and the industrial world by paying attention to ethics/rules/principles from an Islamic perspective. Planning analyzes the world of business and industry that will work together, plans programs in proposals and drafts of activity budgets sourced from national school operational assistance and committees, communicates with the business world and the industrial world; organizing the design of the responsibilities and authorities for each individual position and stipulating these positions to be grouped into certain sections as stated in the decision letter; the control carried out by the school is the existence of a team in charge, the existence of a set time and the form of absence used; the evaluation carried out by the school is to carry out stages in the form of student tests, hold joint meetings related to the MoU agreement and determine the continuity of cooperation with the business world and the industrial world and carry out cost evaluations.